Analisis Kemampuan Berpikir Kritis Mahasiswa Gen Z dalam Mata Kuliah Hidrolika Menggunakan Metode Kuis HOTS pada G-FORM - Kamil, Firmanilah (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
Critical thinking skills are one of the main competencies that must be possessed by students in facing the challenges of an increasingly complex and dynamic world of work. One method that can be used to measure and improve students' critical thinking skills is by using HOTS questions. The use of Google Forms as a medium for HOTS quizzes provides various advantages. The objectives of this research are: 1) To determine the level of critical thinking skills of Gen Z students in the Hydraulics course, and 2) To determine the effectiveness of using HOTS (High Order Thinking Skills) quiz based on Google Forms in measuring and improving students' critical thinking skills in Hydraulics course. This research is a quantitative descriptive research. The number of samples was 54 students. The research instrument was in the form of HOTS questions. The average score for each quiz is as follows: Quiz 1 has an average of about 70.3, Quiz 2 with an average of about 64.8, Quiz 3 shows an average of about 65.7, and Quiz 4 has an average of about 84.5. The level of critical thinking skills of Gen Z students in the course varied, with some students showing high skills from the start, while others needed time to adapt. The use of Google Forms-based HOTS quizzes was effective in measuring and improving students' critical thinking skills. The variation in scores on each quiz reflects the different critical thinking skills among students. The increase in scores from Quiz 1 to Quiz 4 shows that students were able to adapt to this evaluation method and improve their critical thinking skills. Google Forms also provides consistent grading and quick feedback, which helps in the learning process.